The High Security Mechanisms Algorithm of Similarity Metrics for Wireless and Mobile Networking. (20th July 2017) - Wang, Xingwang
Abstract : With the development of human society and the development of Internet of things, wireless and mobile networking have been applied to every field of scientific research and social production. In this scenario, security and privacy have become the decisive factors. The traditional safety mechanisms give criminals an opportunity to exploit. Association rules are an important topic in data mining, and they have a broad application prospect in wireless and mobile networking as they can discover interesting correlations between items hidden in a large number of data. Apriori, the most influential algorithm of association rules mining, needs to scan a database many times, and the efficiency is low when the database is huge. To solve the security mechanisms problem and improve the efficiency, this paper proposes a new algorithm. The new algorithm scans the database only one time and the scale of data to deal with is getting smaller and smaller with the algorithm running. Experiment results show that the new algorithm can efficiently discover useful association rules when applied to data.